Effect of Different Glide Path Establishing Systems on Apically Extruded Debris in Curved Root Canals: An In Vitro Study - Krutika Shekhawat; Himanshi Solanki; Amit Patil; Sheetal Mali; Deepak Sharma; Kishan Agarwal (Journal of Pharmacy and Bioallied Sciences)
Background: Glide path establishment is a critical step in endodontic treatment, particularly in curved root canals, as it facilitates safe and effective canal shaping. The apically extruded debris during this process can cause postoperative complications, including pain and inflammation. Materials and Methods: In this in vitro study, 60 extracted human mandibular molars with curved mesial roots were selected and randomly divided into three groups (n = 20) based on the glide path establishment system used: Group A (manual stainless steel K-files), Group B (rotary PathFiles), and Group C (reciprocating R-Pilot files). Each root canal was instrumented following the manufacturer’s instructions for the respective system. The extruded debris was collected in preweighed Eppendorf tubes during the preparation and subsequently dried and weighed using an analytical balance with a precision of 0.0001 g. Results: The mean weight of apically extruded debris was significantly different among the groups (P < 0.05). Group A (manual K-files) had the highest mean debris extrusion (0.032 ± 0.005 g), followed by Group C (reciprocating R-Pilot files) with 0.021 ± 0.004 g. Group B (rotary PathFiles) exhibited the least amount of debris extrusion (0.015 ± 0.003 g). The differences between all groups were statistically significant (P < 0.05). Conclusion: The type of glide path establishment system significantly affects the amount of apically extruded debris in curved root canals. Rotary PathFiles produced the least debris, suggesting that they may be the most effective in minimizing postoperative complications associated with debris extrusion. Further clinical studies are needed to confirm these findings and to assess their relevance in vivo.